2008
DOI: 10.1002/cncr.23549
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of a novel TNM classification system for upper gastroenteropancreatic neuroendocrine tumors

Abstract: BACKGROUND. Neuroendocrine tumors (NETs) of the gastroenteropancreatic (GEP) system comprise a rare but challenging group of malignant neoplasms and occur at virtually any site of the GEP system. In 2006, a new TNM classification system was proposed for the staging and grading of upper GEP NETs. METHODS. The prognostic relevance of the TNM classification system was analyzed retrospectively in 202 patients from a referral center with histologically proven foregut NET. Patients were classified according to previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
248
3
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(281 citation statements)
references
References 57 publications
17
248
3
13
Order By: Relevance
“…[16][17][18][19] Ekeblad et al 16 reported the analysis of 324 pancreatic endocrine tumors for which diagnosis according to WHO was available in only 241, whereas TNM data were available for 302 and grading for 93 patients. The study did not show any difference between stages I vs II or III, and only demonstrated a significant difference between stage IV (metastatic disease) vs any stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19] Ekeblad et al 16 reported the analysis of 324 pancreatic endocrine tumors for which diagnosis according to WHO was available in only 241, whereas TNM data were available for 302 and grading for 93 patients. The study did not show any difference between stages I vs II or III, and only demonstrated a significant difference between stage IV (metastatic disease) vs any stage.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a significant drop of survival after about 10 years for the WHO category of well-differentiated endocrine tumors in a disease for which only 70% of deaths are expected to be disease-related. 19 Moreover, grading resulted significant only if poorly differentiated endocrine carcinomas were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current WHO grading system, GEP-NETs can be classified according to their Ki-67 proliferation index (MIB-1 staining) into grade 1 (G1), with a Ki-67 index amounting to, or !2%, G2 with a Ki-67 index between 3 and 20% and G3 with a Ki-67 index higher then 20% (4,5). Grading correlates well with the clinical course of patients harbouring these GEP-NETs (6,7,8,9). In addition, clinical features such as the primary localisation of these GEP-NETs, the secretion of excessive amounts of hormones or peptides by these GEP-NETs and the metastatic spread, as reflected by staging of these GEP-NETs, also determine their clinical manifestations and contribute to their prognosis (1,10,11).…”
Section: Introductionmentioning
confidence: 77%
“…Other authors suggest that surgery is indicated in any case because NF-PNETs should always be considered as potentially malignant tumors, and a proper histological examination of the tumor (including the mitotic and Ki-67 indexes) is possible only on the resected specimen. 21,22 Previous studies have reported that several factors are associated with survival, including age, 23,24 tumor size, 9,23,[25][26][27] grade/differentiation, 14,24,25,28 LN status, 25,29 presence of distant metastases, 14,23,24,29 and surgical resection. 14,23 Age has consistently been found to be a powerful predictor of survival in patients undergoing resection of PNETs.…”
Section: Discussionmentioning
confidence: 99%